Gene Expression Profiling of B Cell Lymphoma in Dogs Reveals Dichotomous Metabolic Signatures Distinguished by Oxidative Phosphorylation - Wu, Ying (Front Oncol, 2020)
Gene expression profiling has revealed molecular heterogeneity of diffuse large B cell lymphoma (DLBCL) in both humans and dogs. Two DLBCL subtypes based on cell of origin are generally recognized, germinal center B (GCB)-like and activated B cell (ABC)-like. A pilot study to characterize the transcriptomic phenotype of 11 dogs with multicentric BCL yielded two molecular subtypes distinguished on the basis of genes important in oxidative phosphorylation. We propose a metabolic classification of canine BCL that transcends cell of origin and shows parallels to a similar molecular phenotype in human DLBCL. We thus confirm the validity of this classification scheme across widely divergent mammalian taxa and add to the growing body of literature suggesting cellular and molecular similarities between human and canine non-Hodgkin lymphoma. Our data support a One Health approach to the study of DLBCL, including the advancement of novel therapies of relevance to both canine and human health.